Review of Contemporary Economic Jurisprudence Against Cooperation Agriculture : Study Cooperation Farming in Lumbush Bapereng Tanah Datar District - Rahmawita .; Zainuddin . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
This study aims to examine the contemporary economic jurisprudence review of agricultural cooperation carried out by farmers in Jorong Lumburan Bapereng . As the focus of this research, several research questions were formulated: how is the implementation and forms of agricultural cooperation in Jorong Lumburan Bapereng . After the data is found, it is then discussed using the relevant theory . This research uses a qualitative method with a qualitative descriptive design. Data obtained through interviews with owner land And cultivator . Study This find that implementation cooperation agriculture with method deliver fully to cultivator until harvest . Form of cooperation with system profit sharing, while the seeds, fertilizers and other costs are borne by the farmers . From sight jurisprudence economy implementation And form of cooperation this is similar to mukhabarah . It's just that from an implementation point of view there are things that have the potential to cause unilateral losses , because the land owner fully surrenders to the farmer cultivating the land until harvest